The Interrelationship Between Foreign Direct Investments And Unemployment Rates In Syria. (Latakia University Journal - Economic and Legal Sciences Series, 2021)
In the second half of  the 20th century, the world witnessed an increasing trend towards foreign direct investment as an effective development tool. Especially after the emergence of modern development theories based on the idea that the development deficit in developing countries is not due to the lack of development requirements of material economic resources, but due to the inability of these countries to capitalize resources and exploit them  in such a way that makes them an engine of growth and motivation towards achieving Comprehensive economic development This type of investment is one of the most important economic pillars in contemporary reality, as it plays an important role in the process of economic and social development in countries, because ,advanced technology managerial skills flow through it as a major channel.FDI has played a major role in supporting the growth of the economies of developing countries since the 1980s, taking advantage of the rapid spread of ICTs , the trend towards a market economy in most developing countries and trade liberalization. In terms of capital formation, jobs generation and export expansion, or in terms of access to modern technology needed for economic development.FDI flows into Syria have been increasing since 2003 as a result of the Syrian government's new approach to openness to the domestic and foreign private sector and adaptation of  a market economy.This research will  attempt to know the mutual effects between the net flows of this type of investments and the unemployment rates prevailing in the Syrian economy during the period (1990-2010), Where the study proved that there is no causal relationship in both directions between the net inflows of foreign direct investment to Syria and the unemployment rates during the studied period, whether in the short or long term.